The reconstruction of the bathymetry of the non-existent Krokowo lake - Ptak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The intensive drainage works conducted a few centuries ago in Poland contributed to a significant depletion of the hydrographic network. Currently, there are more and more frequent problems with water stress and the introduction of a programme aiming at the retention development, i.e. through the construction of artificial reservoirs or damming up natural lakes.
Keywords: anthropogenic impact; drainage; water resources; lakes